A Low-Cost Software Defined Radio Based Cognitive Radio Test-Bed for LTE Networks - Suresh Babu, Kolluru; Vemuru, Srikanth (International Journal of Engineering and Technology, 2018)
In this work, we present a low-cost implementation of a Cognitive Radio (CR) test-bed for LTE and LTE-Advanced (LTE-A) Networks. The test-bed setup is implemented using highly integrated Software Defined Radio (SDR) platforms which are well suited for wireless communication. Each transceiver can be configured to work as a primary (resp. secondary) eNodeB or a primary (resp. secondary) user in a Heterogeneous Cognitive Radio framework. In this context, we study the problem of spectrum management in an LTE based heterogeneous network and propose simple distributed algorithms which the secondary eNodeB can employ to efficiently manage the spectral opportunities that arise in such a network. Experimental validation show significant improvement in the secondary link throughput.Â Â